Why in Favor of Tawarruq not Bai’ Al-Inah in Personal Financing Product? - Jamaludin, Azahari (International Journal of Islamic Banking and Finance Research, 2018)
In view of the limited of study with regards to the concept of Bai‟ Al-Inah and Tawwaruq on personal financing, the findings from this study would provide evidence on the understanding of the two concepts, and to determine whether there exists elements of Riba or otherwise in the present medium of personal financing. In addition, the findings of this study can provide a premise whether Tawwaruq is a solution to Bai‟ Al-Inah in personal financing offered by Islamic banksand financial institutions or otherwise. Further, the outcomes may also have some policy implications whereby the policy made can suggest the adoption of Tawwaruq or Bai‟Al-Inah as a best solution to Riba-based personal financing.